Distribution of foot and mouth disease virus serotypes in cattle of Bangladesh (SAARC Journal of Agriculture, 2017)
Foot and mouth disease (FMD) is a highly contagious viral infection in cloven hoofed domestic and wild animals and endemic in many countries of the world including Bangladesh. Clinical investigation was carried out to identify natural cases of FMD and characteristics signs of FMD like salivation, ulceration in oral and pedal tissues and lameness was seen. The specific serotypes of FMD viruses involved in infected cattle were, therefore, identified using reverse transcriptase polymerase chain reaction (RT-PCR). Samples (N=97) from oral lesions was collected from infected cattle from seven divisions of Bangladesh during May to December, 2013. Viral RNA was extracted from the infected oral tissues and FMD virus specific uniplex RT-PCR was designed to detect FMD viruses. Multiplex RT-PCR was adapted to detect serotype specific amplicons. Out of 97 samples tested in uniplex and multiplex RT-PCR, 92 and 90 samples showed amplification reaction for FMD virus and viral serotypes respectively. Among the 90 FMD virus specific positive identification, single infectivity due to FMD viral Serotypes O, A and Asia 1 were seen in 56 (62.2%), 13 (14.4%) and 16 (17.8%) cases respectively. Three cattle (3.3%) were co-infected with FMD viral Serotypes O and Asia 1 and two (2.2%) with FMD viral Serotypes O and A. FMD viral serotype O was dominating all over the country followed by Asia1 and A. Cattle of Bangladesh were infected with FMD viral serotype O, A and Asia 1 alone or in combination. The RT-PCR protocols designed and adapted successfully detected FMD viruses and viral serotypes in a fraction of the time required for virus isolation and serological detection. These RT-PCR protocols can be used for rapid serotyping of FMD viruses from filed infectivity and selection of vaccine viruses.SAARC J. Agri., 15(1): 33-42 (2017)